UTILIZING FOUNDER’S PERSONAL BRANDING AS PROPOSED STRATEGY TO INCREASE BRAND AWARENESS: CASE STUDY IN LOUISSE CHOICE BEAUTY - Annisa Fara Nabila; Novika Candra Astuti (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This research aims to formulate and propose a digital marketing strategy that can be used by Louisse Choice Beauty to increase brand awareness given that the current state of Louisse Choice Beauty has lower engagement compared to the popularity of its founder, Louisse Scarlett. This research seeks to utilize founder’s personal branding as a digital marketing strategy. The method used in this research is a qualitative method that combines primary and secondary data to provide an in-depth understanding of the topic under the study. Data collection was carried out in two events, namely primary data collection conducted by in-depth interviews with internal and external stakeholders including founders, marketing leaders, digital marketing teams, and consumers. Then secondary data collection in the form of document studies of industry reports on the beauty market, academic journals, beauty market phenomenon, and media coverage and consumer reviews on social media and marketplaces. The theory used in this research is the AFI framework which used as the basis for preparing digital marketing strategies. In the analysis stage, Porter’s Five Forces theory is used to analyze external environments and VRIO with 4P are used to analyze internal conditions. At the formulation stage, TOWS Matrix is used to formulate a digital marketing strategy by aligning the strengths and weaknesses of Louisse Choice Beauty. After that, the marketing strategy was formulated at the implementation stage using personal branding as main approach. The RACE framework is used at this stage to check the success indicators of the digital marketing strategy. This research also used brand awareness theory. The result of this research, Louisse Choice Beauty is advised to integrate the founder’s personal branding into its digital marketing strategy to represent a rare and valuable resource in creating authentic emotional connections with consumers. The team should create a content calendar to create consistency and align content with storytelling, product education, and founder engagement on social commerce platforms such as TikTok Shop and Instagram. These targeted and organized strategies were able to increase brand awareness of Louisse Choice Beauty.